Social Support Relationship with Quality Life of Breast Cancer Patients in The Community Care for Cancer Rose Pink North Sumatra Year 2022 - Sitinjak, Nelly Verawati; Novitarum, Lilis; Lindawati F Tampubolon (International Journal on Health and Medical Sciences, 2024)
Breast cancer is a non-communicable disease and treatment is carried out on a scale. In doing treatment patients with breast cancer need social support such as support from family, relatives or close friends. The social support that these patients get can improve medication adherence and improve the quality of life of patients with breast cancer. This study aims to analyze the relationship between social support and quality of life in breast cancer patients in the Rose Pink Care Community, Nort Sumatra in 2022. The research method user is a cprrelation research design with a Cross Sectional approach. The samping technique is purposive sampling with 30 respondents. The data is collected using a questionnaire and the statistical test used is the Pearson Product Moment Correlation Test. The results of p-value= 0.383 (p>0.05) means that there is no relationship between social support and the quality of life of breast cancer patients at Rose Pink Cancer Care Community, North Sumatra 2022. It is hoped that this research will serve as a reference for families of breast cancer patients to provide support/motivation to patients with breast cancer.